A corpus-based study on the cognitive construction of security in discourse - Hu, Chajuan (Frontiers in Psychology, 2023)
A discourse-based approach to understand security has been explored in the study of International Relations, yet how other agents rather than the political agents speak to conceptualize the emotive appeal in unconventional security issues is less discussed. This corpus-based cognitive critical discourse study examines security by combining the International Relations’ theory of securitization with the proximization approach in Critical Discourse Studies. As a case study, texts concerning Confucius Institutes on National Association of Scholars’ official website from 2014 to 2020 were collected to discuss how the threat is constructed discursively and cognitively for an endeavor to influence the public as well as the political decision-making process. The corpus was further divided into two sub-corpora in order to expose the difference in their cognitive construction of Confucius Institutes. The findings show that the American academia deliver a bottom-up securitizing move by constructing education security discourse on Confucius Institutes in the initial process, yet later the whole-of-society security narratives interacting with a top-down securitizing move from the political agents has been adopted. As is indicated by the corpus statistics, the concerned discourses are discursively constructed by following the ‘Self-Other’ dichotomy security narratives, in which Confucius Institutes are cognitively transformed from an academic issue to a national security issue and legitimized through proximization in the spatial, temporal and axiological dimensions.